2014
DOI: 10.1007/s12288-014-0373-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Hemoglobinopathies in West Bengal, India: A CE-HPLC Study on 10407 Subjects

Abstract: Hemoglobinopathies are common genetic disorders of haemoglobin. Identification of these disorders is immensely important epidemiologically and they can be prevented by population screening. The present study was carried out to evaluate the spectrum of hemoglobinopathies in the state of West Bengal by the cation-exchange high-performance liquid chromatography (CE-HPLC). A retrospective, single-center, cross-sectional study was conducted on consecutive 10,407 participants. Out of 10,407 subjects, 8,898 (85.5 %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…In contrary to these findings, mean RDW was found to increase in all the subjects with Haemoglobin variants. The same findings were also reported by Baruah et al 13] and Mukhopadhyay et al [14] . Increase in RDW is not a usual finding of pure haemoglobinopathies.…”
Section: Discussionsupporting
confidence: 89%
“…In contrary to these findings, mean RDW was found to increase in all the subjects with Haemoglobin variants. The same findings were also reported by Baruah et al 13] and Mukhopadhyay et al [14] . Increase in RDW is not a usual finding of pure haemoglobinopathies.…”
Section: Discussionsupporting
confidence: 89%
“…Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively. Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] found beta thalassemia trait cases to be 8.9 %,18.1 %,10.38 % and 5.6 % respectively. Our findings are comparable to these different Indian studies.…”
Section: Discussionmentioning
confidence: 95%
“…Different studies by Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] have taken 2600, 800, 35413 and 10407 cases respectively for their study. Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1] At present, approximately 250 million people constituting 4.5% of the world population are carriers of a hemoglobinopathy gene. [2] India constitutes 10% of thalassemia in the world with 10,000 children being born with thalassemia major every year. The frequency range of beta thalassemia is 3.5% to 15% in Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In newborns, timely detection of various abnormal Hb can prevent occurrence of more serious disorders like thalassemia major. [2] High performance liquid chromatography (HPLC) has been proved to be a sensitive, specific, and reliable alternative to electrophoresis. It helps in direct identification and quantification of both normal Hb and abnormal Hb types.…”
Section: Introductionmentioning
confidence: 99%